Avaliação da ansiedade como preditor de complicações pós operatórias em pacientes submetidos a cirurgia de terceiros molares - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This study aimed to verify whether preoperative anxiety in different degrees and extensions of third molar surgeries could interfere with the patient self-perception of postoperative pain, edema and trismus. This study receives the classification of observational, prospective and exploratory. Anxiety levels were obtained using the State-Trait Anxiety Inventory (STAI). The levels of pain and edema were self-assessed using a diary containing a visual and numerical scale (0-100). Trismus was self-assessed using a six-point ordinal (verbal descriptive) scale (0-5). Data related to surgical difficulty were also obtained, through the surgeon's view, using a six-point ordinal (verbal descriptive) scale (0-5). Additional data related to systemic conditions were also obtained, such as the ASA Classification (American Society of Anesthesiologists) adapted to dentistry by Medical Risk Related History (EMRRH), heart rate (HR), blood pressure (PA) and a handheld electrocardiogram (ECG) analysis. In addition, trans-surgical data such as time, quantity of anesthetics, among other variables, were obtained. Data on the impact of the prescription on the main variables, anxiety, pain, edema and trismus were explored. Postoperative pain showed correlations with the highest levels of anxiety state (STAI-State). Anxiety (STAI – Trait and State) did not influence the perception of edema and trismus. As for the use of antibiotics, it was more prescribed to the group that removed two or more teeth. The use of antibiotics prevented higher rates of trismus until the third postoperative day. As for the prescription of anxiolytics, they were correctly prescribed for patients who had higher levels of anxiety state (STAI-State). The use of corticosteroids in a single prophylactic dose did not show statistically significant differences for pain, edema and mouth opening rates. The greater the surgical difficulty described by the surgeon, the higher was the trismus until the third postoperative day and greater was the perception of edema until the sixth postoperative day. The duration of surgery did not show associations with postoperative pain, however, it did show associations with the perception of edema and trismus, mainly, until the fifth postoperative day. The handheld ECG was able to detect an increase in heart rate in pre-surgical patients, indicating physiological changes related to stress or anxiety, however, this finding did not show any association with the STAI values. Within the limitations of the study, it was possible to observe that the state of anxiety seems to interfere with the perception of postoperative pain.
Keywords: Ansiedade; Cirurgia bucal; Complicações pós-operatórias; Dor; Trismo; Edema; Anxiety; Oral surgery; Postoperative complication; Pain; Trismus; Edema; CNPQ::CIENCIAS DA SAUDE